The effect of aerobic training and consumption of iron and vitamin C supplements on blood iron indices among active females - Masoumeh Hosseini; Masoumeh Azizpour; Abdolrasoul Daneshjoo (فصلنامه ابن سینا)
Background: Iron excretion increases during sport activities and menstruation. However, consumption iron supplements along with vitamin C improves iron stores. The purpose of this study was to investigate the effect of aerobic training, consumption of iron, and vitamin C on blood iron indices among females with iron deficiency and with at least six months sport activities background. Materials and methods: In this semi-experimental study, 32 volunteer females aged 35±4.4 years were selected and randomly divided into four groups including a control group and three training groups (T1: without supplements; T2: + iron; T3: + iron + vitamin C). The training program consisted of eight weeks ،three sessions per week and 60 minutes per session (jogging, low impact aerobic training chain) with an intensity of 70% of the target heart rate. After per session of exercise in T2 and T3 groups subjects consumed 100 mg pill of ferrous sulfate and in T3 group subjects consumed 500 mg chewable vitamin C pill. Before and after the research protocol, blood hemoglobin, hematocrit, red blood cell, ferritin and transferrin measured by using specific methods. Multivariate analysis of variance was used. Results: The results showed differences in the hemoglobin, hematocrit, red blood cell, ferritin and transferrin variables between T3 and control group which were significant for hemoglobin (p=.006), red blood cell (p=.008), and ferritin (p=.003) variables. Conclusion: Aerobic training with consuming iron supplementation and vitamin C can improve some hematological indices in females.